BAHASA NEGARA YANG TERABAIKAN POLA BARU BERKOMUNIKASI DAN MARTABAT BAHASA INDONESIA - Anggraini, Siti (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2015)
The important of Information Technology mostly in social media now often effect the common use in Indonesian language. The new pattern of a communication made side effect for the written and pronounciation of the lan-guage itself especially often use by the university students. The Bahasa Indonesika as the national language must strictly use in a good and right way.